Identification of novel mutations in preaxial polydactyly patients through whole‐exome sequencing - Wang, Tao (Mol Genet Genomic Med, 2019)
BACKGROUND: Polydactyly is one of the most common hereditary limb malformation characterized by additional digits in hands and/or feet. With extra fingers/toes, which could be very problematic, polydactyly patients are usually treated in early childhood by removing of extra digits with surgery. Genetically, polydactyly is caused by mutations of genes that involve in digit formation. METHODS: In the current report, we performed genetic analysis for polydactyly using DNA samples from a cohort of 20 Chinese patients. All patients show preaxial polydactyly in one of their hands. RESULTS: With whole‐exome sequencing (WES), we have identified two novel heterozygous mutations c.G2844A in GLI3 gene (OMIM 165240) and c.1409_1410del in EVC gene (OMIM 604831). Compound heterozygous mutations that affect KIAA0586 gene (OMIM 610178) are also detected. Proteins encoded by the genes have important roles in primary cilia and regulate sonic hedgehog signaling pathway. CONCLUSION: Our study highlights the important roles of primary cilia in limb development, and helps to further understand the molecular mechanisms for polydactyly formation.